Analisis Level Pemahaman Membaca Siswa Kelas VII SMP Negeri 1 Cibalong Pada Teks Narasi Berdasarkan Taksonomi Barrett - Erni Fitriani; Asep Nurjamin (Yayasan Al-Afif, 2026)
Reading comprehension is an essential competence in learning Indonesian, especially in understanding narrative texts. However, some students still experience difficulties in comprehending explicit and implicit meanings and in evaluating the content of texts. These problems indicate the need for studies that analyze students’ reading comprehension based on cognitive levels. This study aims to analyze the level of reading comprehension ability of seventh-grade students at SMP Negeri 1 Cibalong in narrative texts based on Barrett’s Taxonomy and to describe the characteristics of students’ comprehension at each level. This study employed a quantitative approach with a descriptive design. The subjects consisted of 32 students from class VII D selected through purposive sampling. Data were collected through a written test consisting of five essay questions representing the literal, reorganization, inferential, evaluative, and appreciative levels. The data were analyzed using descriptive quantitative techniques by calculating scores, mean values, and percentage categories of students’ abilities. The results showed that the students’ average score was 80, which falls into the Good category. A total of 43.75% of students were in the Very Good category, 34.38% in the Good category, and 21.88% in the Fair category. The highest achievement was found at the literal and reorganization levels, while variations in ability were still observed at the inferential, evaluative, and appreciative levels. These findings indicate the need to strengthen learning activities that emphasize the development of critical and reflective thinking skills. Kata kunci: reading comprehension, narrative text, Barrett’s Taxonomy, junior high school students, reading literacy.